Pengembangan Sumber Daya Pendidik - Mufidah, Yenny Imroatul (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
Educators in the education process play a strategic role, especially in efforts to shape the character of the nation through the development of personality and desired values. The urgency of educators in the learning process is illustrated in the Arabic expression that was delivered by A. Malik Fadjar,